Vertical potential gradient profile under point discharge current and wind - PRASAD, M.; VERMA , T. S.; VARSHNEYA, N. C. (MAUSAM, 1976)
An attempt is made to study the influence of winds and point discharge current on vertical electric potential gradient profile in thunderstorms in the atmosphere. This is further extended to the case of precipitation where falling drops possess charge but do not interact with ions. The profiles under different wind speeds are plotted and compared.